Husserl, Cohen e Cassirer - Laino, Luigi (Bollettino Filosofico, 2024)
In this essay, I will discuss the concept of historical teleology in Husserl, Cohen and Cassirer. I will distinguish between a “strong” and a “weak” teleology to define two paths that seem to enliven transcendental philosophy. On the one hand, the strong option is underpinned by more general hypotheses on the relationship concerning “consciousness” and “reality”, “thought” and “being”, as well as it gives rise to an “archaeo-teleology”; on the other hand, the weak option tones down the substantial unity of this framework and enables a comparative approach. Therefore, I will show that the most important difference between strong and weak teleology revolves around the emphasis respectively put on the terminus a quo and the terminus ad quem, but I will also draw attention to the intertwining of these two strategies. Keywords: Culture, Origin, Science, Teleology, Weltgeschichte